Practical Significance Of The Mechanism Of Metabolism In Microorganisms (Eurasian Journal of Humanities and Social Sciences, 2026)
This article highlights the biological and practical significance of metabolic processes in microorganisms. The metabolic activity of microorganisms and their important role in the food industry, agriculture, biotechnology, pharmaceuticals, and ecology were analyzed. The main stages of metabolic processes, enzymatic reactions, mechanisms of energy production, and their industrial applications were scientifically described. In addition, the practical significance of aerobic and anaerobic metabolism, biosynthesis, and biodegradation processes of microorganisms was demonstrated.